1972
DOI: 10.1111/j.1476-5381.1972.tb06854.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lithium salts on the urinary excretion of α‐oxoglutarate in man

Abstract: Summary1. Lithium ions in therapeutic doses cause an increase in the renal excretion of a-oxoglutarate and glutaric acid. 2. The excretion is probably due to reduced renal tubular reabsorption. 3. Neither citrate, lactate nor pyruvate excretion rises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Lithium also acts as a potent inhibitor of succinate transport by NaDC-1 when Na ϩ is present, with an apparent K i of 2 mM (3,11). In humans and rodents, treatment with Li ϩ leads to rapid increases in urinary concentrations of Krebs cycle intermediates (4,27). In this study, Li ϩ behaved as a mixed-type inhibitor of NaDC-1.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Lithium also acts as a potent inhibitor of succinate transport by NaDC-1 when Na ϩ is present, with an apparent K i of 2 mM (3,11). In humans and rodents, treatment with Li ϩ leads to rapid increases in urinary concentrations of Krebs cycle intermediates (4,27). In this study, Li ϩ behaved as a mixed-type inhibitor of NaDC-1.…”
Section: Discussionmentioning
confidence: 63%
“…The Na ϩ -dicarboxylate cotransporter reabsorbs a wide range of di-and tricarboxylic acids in the form of divalent anions. This transporter is sensitive to inhibition by lithium (3), and patients receiving therapeutic doses of lithium exhibit increased renal excretion of ␣-ketoglutarate and glutarate (4). The cDNA coding for the rabbit renal Na ϩ /dicarboxylate cotransporter, NaDC-1, 1 has been cloned and sequenced (5), and the protein has been identified in renal brush border membranes (6).…”
mentioning
confidence: 99%
“…5) ii from 1-sec uptakes. Note that the membranes were not voltgroup (1,3,5) that Li ihibits the active reuptake ofdicarboxylic iped in this experiment. The J vs. Li data were fitted to a modacids by the renal tubule.…”
Section: + Tmentioning
confidence: 99%
“…Within minutes, Li+ at therapeutic doses increases renal excretion of a-ketoglutarate and succinate by 1-2 orders ofmagnitude. Jenner's group (3)(4)(5) speculated that Li+ increased excretion by inhibiting the active reuptake of the dicarboxylic acids by the renal tubule.…”
mentioning
confidence: 99%
“…Previous investigations speculated that lithium increased renal excretion of dicar boxylic acids by reducing renal tubular reabsorption (13,14). Recently, Wright et al demonstrated that lithium acted as a potent inhibitor of the Na+-dependent uptake of a dicarboxylic acid, succinate, into renal luminal membrane vesicles, but did not inhibit Na+-coupled glucose and amino acid transport into the vesicles (15).…”
mentioning
confidence: 99%